If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3y = 3 + -4y Solving 4 + -3y = 3 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 4 + -3y + 4y = 3 + -4y + 4y Combine like terms: -3y + 4y = 1y 4 + 1y = 3 + -4y + 4y Combine like terms: -4y + 4y = 0 4 + 1y = 3 + 0 4 + 1y = 3 Add '-4' to each side of the equation. 4 + -4 + 1y = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 1y = 3 + -4 1y = 3 + -4 Combine like terms: 3 + -4 = -1 1y = -1 Divide each side by '1'. y = -1 Simplifying y = -1
| 5b+8-6b= | | 3x-5/3=96 | | 100=(4*w)*w | | 41790=5(210t) | | 100=(4xw)xw | | -n-21=8-3(n+7) | | 8x-10=7x+2 | | 13-4=x | | x^2-3=a | | ((-5)*c)+(8*c)= | | 2a-8=4(3a+1)-7 | | 2x-19=3x | | -7a+8b=25 | | x^2+.4+3=0 | | 4sin^2x-4sinx-9=0 | | 4x+5=48 | | 7+x=-4x+117 | | 3s-5= | | -5x-17/-4=-7 | | 3(s-5)= | | (x-2)(x-i)=0 | | 12x-48=36 | | 3cosx-2x=0 | | (2b-68)+(b-3)=180 | | 5t+20a=0 | | 26-9y=-4 | | 2w+8=10 | | 6x+7=x+47 | | (8c-6)-(c+7)= | | 4x+2(4-3x)=2 | | 111=3x-15 | | 5(u+8)-8u=25 |